Mo birget soadis (how to cope with war): Adaptation and resistance in Sámi relations to Germans in wartime Sápmi, Norway and Finland. Issue 1 (1st January 2020) - Evjen, Bjørg; Lehtola, Veli-Pekka
Abstract : The article studies the Sámi experiences during the 'German era' in Norway and Finland, 1940–1944, before the Lapland War. The Germans ruled as occupiers in Norway, but had no jurisdiction over the civilians in Finland, their brothers-in-arms. In general, however, encounters between the local people and the Germans appear to have been cordial in both countries. Concerning the role of racial ideology, it seems that the Norwegian Nazis had more negative opinions of the Sámi than the occupiers, while in Finland the racial issues were not discussed. The German forces demonstrated respect for the reindeer herders as communicators of important knowledge concerning survival in the Arctic. The herders also possessed valuable meat reserves. Contrary to this, other Sámi groups, such as the Sea Sámi in Norway, were ignored by the Germans, resulting in a forceful exploitation of sea fishing. Through the North Sámi concept birget (coping with), we analyse how the Sámi both resisted and adapted to the situation. The cross-border area of Norway and Sweden is described in the article as an exceptional arena for transnational reindeer herding, but also for the resistance movement between an occupied and a neutral state.